2018
DOI: 10.1007/s10208-018-9388-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Based Methods for Partially Observed Chaotic Systems

Abstract: In this paper we consider filtering and smoothing of partially observed chaotic dynamical systems that are discretely observed, with an additive Gaussian noise in the observation. These models are found in a wide variety of real applications and include the Lorenz 96' model. In the context of a fixed observation interval T , observation time step h and Gaussian observation variance σ 2 Z , we show under assumptions that the filter and smoother are well approximated by a Gaussian with high probability when h an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…In [52], it is shown that the MAP estimator for the smoother has some desirable theoretical properties. In particular, in the small-noise/high-frequency scenario (with T fixed, and σ √ h → 0), under some conditions, MAP is asymptotically optimal in mean-square error.…”
Section: Methods Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In [52], it is shown that the MAP estimator for the smoother has some desirable theoretical properties. In particular, in the small-noise/high-frequency scenario (with T fixed, and σ √ h → 0), under some conditions, MAP is asymptotically optimal in mean-square error.…”
Section: Methods Overviewmentioning
confidence: 99%
“…The second reason is that a Gaussian distribution propagated through non-linear dynamics for longer and longer intervals of length bT becomes highly non-Gaussian for large values of b, so the resulting background distribution can lead to poorer results than using smaller values of b. Reminiscent to 4D-Var, at time t (m−b)k we always start off the procedure with the same background covariance B 0 . In [52] it was shown -under certain assumptions -that for a class of non-linear dynamical systems, for a fixed observation window T , if R i = O(σ 2 ) and σ √ h is sufficiently small (h is the observation time step) then the smoothing and filtering distributions can indeed be well approximated by Gaussian laws. Following the ideas behind (3.5), an approximation of the Hessian of J, evaluated at the MAP given data y • (m−1)k:mk−1 is given as…”
Section: D-var Filtering With Flow-dependent Covariancementioning
confidence: 99%
See 3 more Smart Citations